EPID-16. DIFFUSE LEPTOMENINGEAL GLIONEURONAL TUMOR IN PEDIATRIC PATIENTS: A QUANTITATIVE EXPLORATION. (12th November 2021) - Lu, Victor; Di, Long; Daniels, David; Maher, Ossama; Niazi, Toba
Abstract: BACKGROUND: Diffuse leptomeningeal glioneuronal tumor (DLGNT), also known as oligodendrogliomatosis, is a rare neuro-oncologic condition along the neuraxis that remains poorly understood in children. We sought to describe our institutional experience and quantitively summarize the clinical survival and prognostic features of DLGNT in the pediatric population across the contemporary literature. METHODS: We report four institutional cases of pediatric DLGNT diagnosed between 2000-2020 based on retrospective review of our records, and performed a comprehensive literature search for published cases from 2000 onwards to create an integrated cohort for analysis. Kaplan-Meier estimations, Fisher's exact test, and logistic regression were utilized to interrogate the data. RESULTS: Our overall integrated cohort consisted of 54 pediatric DLGNT patients, with 19 (35%) female and 35 (65%) male patients diagnosed at an average age of 6.4 years (range, 1.3-17 years) by means of surgical biopsy. Chemotherapy was used in 45 cases (83%), and mean follow-up time of 54 months (range, 3-204). Across the entire cohort, overall survival 1 month after diagnosis was 96% (95% CI 86-99%), and by 10 years was 69% (95% CI 49-82%). On multivariate analysis of complete data, chemotherapy treatment (HR=0.23, P=0.04) was statistically predictive of longer overall survival. When including limited data, longer duration of symptoms by presentation (HR=1.03, P=0.03) was statistically predictive of shorter overall survival. CONCLUSIONS: This is the first quantitative study of pediatric DLGNT clinical course. More than 2-out-of-3 pediatric DLGNT patients survive beyond one decade. Chemotherapy is statistically associated with longer survival in DLGNT pediatric patients and should form the core of any treatment regimen in this setting. Early detection by means of judicious imaging and surgical biopsy for tissue diagnosis can lead to earlier treatment and likely superior outcomes.